Influence of Workload, Information Technology Usage, and Work Environment on Employee Performance at Cileunyi District Office, Bandung Regency - Qodarisman, Rahmat; Jaya, Rama Chandra (Dinasti International Journal of Management Science, 2025)
Human resources constitute a critical element in organizational functioning, as one of the primary determinants of an organization's success is the managerial capacity to coordinate all employees, enabling them to contribute effectively to every operational process in pursuit of established goals. Fundamentally, the advancement or even regression of an organization is determined by the quality of its human capital. This study aims to analyze the influence of workload, information technology usage, and work environment on employee performance at the Cileunyi District Office. A quantitative approach employing descriptive and verificative methods was utilized. Data were collected via questionnaires distributed to all 43 employees and analyzed using multiple linear regression with SPSS version 30. Field findings indicate that employee performance at Cileunyi District remains suboptimal, attributable to a workload imbalance relative to staff numbers, uneven employee proficiency and comprehension in utilizing information technology, and a work environment that is no longer adequate. The derived regression equation, Y = 11.058 + 0.903X₁ + 1.050X₂ + 0.317X₃ + e, demonstrates that all three variables exert a positive influence on employee performance, albeit with varying degrees of impact. Specifically, information technology usage and workload show substantially higher coefficients, whereas the work environment exhibits a comparatively lower coefficient. A correlation coefficient (R) of 0.863 indicates a very strong relationship between workload, information technology usage, work environment, and employee performance. Furthermore, the coefficient of determination (R²) reveals that the combined contribution of these three variables accounts for 74.5% of the variance in employee performance, while the remaining 25.5% is influenced by other factors not examined in this study.